Sustainability Islamic Business: Risk Management Review - Amriyah, Yassirly; Ismawati, Fadila Nur; Pranata, Dedy; Bhakti, Rezsa Lingga; Asiyah, Binti Nur; Hidayat, Muhammad Syahrul (Majapahit Journal of Islamic Finance and Management, 2024)
Islamic business has the phenomenon of being easy to grow and easy to leave. This study aims to analyze the sustainability of Sharia business from the perspective of risk management. This research uses a qualitative approach with a type of literature study employing the PRISMA Method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Data was collected from various literature, both from books and related journals. This study introduces the Islamic view on risk management, the urgency of risk management for Sharia businesses, and the implementation of Islamic principles that emphasize the blessings and pleasure of Allah SWT in its operations. The main findings of this study indicate that the application of risk management following Sharia principles can enhance the sustainability of Sharia businesses. The practical implications of this study guide for Sharia business practitioners to consistently manage risks, thereby achieving business sustainability. As a result, businesses can endure and provide benefits for economic circulation in the community.